Peningkatan Gotong Royong Siswa melalui Model Project Based Learning Berbantuan Media Audiovisual di Fase B Kelas 3 SDN Sumber 3 Surakarta - Widuri Larasati (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to improve the affective learning outcomes in the dimension of collaboration (gotong royong), as well as cognitive and psychomotor learning outcomes of third-grade students at SDN Sumber 3 Surakarta through the application of the Project Based Learning model assisted by audiovisual media. The urgency of selecting this topic stems from the low levels of collaboration and student participation in cooperative activities, which negatively impact social interactions and learning outcomes. Addressing this issue is critical to fostering Pancasila Student Profiles with cooperative and integrity-based characteristics. This classroom action research was conducted in two cycles. The results show significant improvements in all three learning aspects. The collaboration dimension saw a 12.5% increase, with 67% of students classified as "Proficient". Cognitive learning outcomes improved by 10%, with 87% of students reaching the "Proficient" level. Psychomotor learning outcomes also increased by 5%, with 67% of students classified as "Proficient". These findings demonstrate that PBL assisted by audiovisual media is effective in fostering students' affective, cognitive, and psychomotor development while promoting active participation in project-based learning.